Phenomenon oflifelong professional education as a means of achievements of «acme» - Dyba Tetyana (Освітологія, 2015)
Inthe article the concept of “lifelong education” was analyzed as well asits main characteristics and features.The composition (formal, unformal, informal education) was specificated and lifelong education system was characterized.The professional’s acmeological characteristics were analyzed together withone’s “acme” conditions of formation, development and achievement.The phenomenology of lifelong professional education was found and the qualitative characteristics of one’s development in the educational system in the process of training within the higher education institution were identified as well as conditions of future specialist’s acme-competency potential development.Acme in professional development is defined as the highest level for a certain person in his professional development at a certain stage of life’s journey, which is manifested in the maximum mobilization, implementation of one’s professional abilities, possibilities and reserves.Professional acme may have varying degrees of social and personal significance.